Ozonation as an effective way to stabilize new kinds of fermentation media used in biotechnological production of liquid fuel additives. Issue 1 (December 2016) - Dziugan, Piotr; Balcerek, Maria; Binczarski, Michal; Kregiel, Dorota; Kucner, Marcin; Kunicka-Styczynska, Alina; Pielech-Przybylska, Katarzyna; Smigielski, Krzysztof; Witonska, Izabela
Abstract Background Intermediates from processing sugar beets are considered an attractive feedstock for ethanol fermentation due to their high fermentable sugar content. In particular, medium prepared from raw sugar beet juice seems to be suitable for use in fermentation processes, but it is microbiologically unstable and requires sterilization. Results This study investigates the effect of ozone treatment on the activity of microbial cells fromBacillus subtilis, Leuconostoc mesenteroides, Geobacillus stearothermophilus, Candida vini, andAspergillus brasiliensis in raw sugar beet juice. Raw sugar beet juice contaminated with 105 cfu/mL of the microbial strains was treated with gaseous ozone (ozone concentration in the oxygen stream 0.1 g O3 /L O2, flow rate 6 L/h, 10–30 min, 18–20 °C). The number of microflora decreased to 0 cfu/mL after 30 min of ozone treatment in all studied samples. Conclusions Medium prepared from raw sugar beet juice and sterilized by ozonation is suitable for use in fermentation processes.